The Art of Adaptation: From Folk Literature to the Age-Appropriate Visual Media - Santi Sidhartani; Muhammad Iqbal Qeis; Dendi Pratama (Cultural Syndrome, 2019)
The art of adaptation is a process to translate the art form fromone mediainto another.Folklores as a form of media that express the experience and beliefs that was shared amongst the society living in a certain region are usually passeddown from the older generation to the younger generation by word of mouth orthoughoral tradition. Althoughsome of thefolklores havebeen compiledand translated in the form of folk literature andare transcribedin books and written media, these folk literaturesgenerally consist oftexts with little visuals. This is a problem since the main target of folklores is usually children who are more attracted to colorful and rich world of illustration rather than a text-filled literary book. This paper aims to describe the process involved in the art of adaptation that transforms folk literature into a more age-appropriate visualmediaforchildren as an effort to preserve the tradition of folklore in society. The conclusion shows that the process involved a deep understanding of the folklore, not only the story but also the characters and the background location depictedin order to design an appealing visual media thatretainsthe cultural values shared within the society